Enhancing the Understanding of the Pronunciation of Arabic Pharyngealized Plosive Sounds via Acoustic Phonetic Approach - et al., Majdan Paharal Radzi (International Journal of Advanced Science and Technology, 2019)
Experimental Phonetics is a branch of phonetics study that uses experimental tools to analyze data. In general, this approach looks at the physical features of a language sound in either segmental or suprasegmental ways and attempts to create a more accurate description of a sound. Based on previous literature studies, acoustic phonetics approach has not made its mark among Arabic phonetics researchers. Even though, there are some acoustic phonetics studies that have highlighted the distinct features of the plosive sound, it has not yet reached the significant amount of importance. Therefore, as a conceptual article, this paper discussed the physical features of plosive pharyngealized sound in Arabic using Voice Onset Time (a common acoustic cue used by other phonetic researchers). The acoustic analysis of plosive sound using Voice Onset Time was first introduced by Lisker and Abramson in 1964. It is hoped that this study will contribute the enrichment of knowledge and will successfully highlight acoustic phonetics knowledge in different dimension.